2013
DOI: 10.1371/journal.pone.0059879
|View full text |Cite
|
Sign up to set email alerts
|

Dual Phosphoinositide 3-Kinase/Mammalian Target of Rapamycin Inhibitor NVP-BEZ235 Has a Therapeutic Potential and Sensitizes Cisplatin in Nasopharyngeal Carcinoma

Abstract: Phosphoinositide 3-kinase (PI3K)/AKT/mammalian target of rapamycin inhibitor (mTOR) pathway is often constitutively activated in human tumor cells and thus has been considered as a promising drug target. To ascertain a therapeutical approach of nasopharyngeal carcinoma (NPC), we hypothesized NVP-BEZ235, a novel and potent imidazo[4,5-c] quinolone derivative, that dually inhibits both PI3K and mTOR kinases activities, had antitumor activity in NPC. Expectedly, we found that NVP-BEZ235 selectively inhibited prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 50 publications
(49 reference statements)
4
40
0
Order By: Relevance
“…In this study, GSK2126458 or PKI-587 reduced the levels of phosphorylated Akt, mTOR, S6, and 4EBP1 in a time-and concentration-dependent manner, consistent with other reports in NPC (23,37,38). In addition, we found that very low concentrations of GSK2126458 and PKI-587 could effectively inhibit the migration and invasion of NPC cells, which may be associated with reduced EMT phenotypic expression, indicating the high efficacy of these compounds.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, GSK2126458 or PKI-587 reduced the levels of phosphorylated Akt, mTOR, S6, and 4EBP1 in a time-and concentration-dependent manner, consistent with other reports in NPC (23,37,38). In addition, we found that very low concentrations of GSK2126458 and PKI-587 could effectively inhibit the migration and invasion of NPC cells, which may be associated with reduced EMT phenotypic expression, indicating the high efficacy of these compounds.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, we reported that Akt expression in NPC cells and biopsies from patients with NPC could be increased by IR, which is associated with metastasis, suggesting that the PI3K/mTOR pathway might be an ideal therapeutic target in NPC (22). Preclinical studies have demonstrated that targeting the PI3K/mTOR pathway by a dual PI3K/mTOR inhibitor, NVP-BEZ235, sensitized the antitumor effect of cisplatin in NPC (23). However, there is little data about the effect of inhibition of PI3K/Akt/mTOR signaling on tumor progression and radiosensitivity in NPC.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Furthermore, dual PI3K/mTOR inhibition has also been shown to downregulate Mcl-1 levels in other tumors. [39][40][41][42] It has been proposed that PI3K/mTOR inhibition leads to a downregulation of Mcl-1 due to a block in cap-dependent translation. 23,43 Our studies show that PI3K inhibition using multiple pan-specific and isoform-selective PI3K inhibitors in either AML cell lines or primary AML blasts had very little impact on Mcl-1 levels (Figures 2-3 For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…As a PI3K/mTOR inhibitor, NVP-BEZ235 strongly blocks Akt kinase activity, which results in the aforementioned Akt function becoming inefficient, and thereby induces cell cycle arrest in the G1 phase (10). In addition, NVP-BEZ235 has also been associated with the positive regulation of mid-and late-G1 phase cyclin/Cdk activity through the phosphorylation and inactivation of the Cdk inhibitor p21 in MKL-1 cells (29,30). Overall, the decrease in cyclin D1 and increase in p21 and p27 levels may contribute to the G1 cell cycle arrest observed in NVP-BEZ235-treated MKL-1 cells.…”
Section: A B C Dmentioning
confidence: 99%